Analysis of alpha-cypermethrin pesticide residues along the value chain of tomato from Laikipia County, Kenya - Obar, J.A.; Kwoba, E.; Omosa, Esther; Ekaya, Wellington; Fèvre, Eric M.; Onono, J. (Wiley, 2026)
BACKGROUND In Kenya, the extensive use of agrochemicals in fruits and vegetable farming raises concerns about pesticide residues in agricultural products including tomato fruits. There are still a number of highly hazardous pesticides including mancozeb, glyphosate acid, chlorpyrifos, acephate and cypermethrin amongst many others that are still used in Kenya despite being banned in Europe due to harmful effects on humans and other animals. This study aimed to evaluate the residual levels of cypermethrin pesticide in locally produced tomato in Laikipia County, Kenya. Also, the study identified some practices that lead to pesticide residual levels in tomatoes. A total of 82 tomato samples were analyzed for pesticide residues following extraction using QuEChERS method and analyzed for the presence of synthetic pyrethroids (cis- and trans-alpha-cypermethrins) pesticides using gas chromatography–mass spectrometry (GC–MS).